2021
DOI: 10.1002/joc.7445
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructed precipitation in the Lohit River basin, southern Tibetan Plateau since 1720 CE and its weak linkages with monsoon‐season Brahmaputra discharge

Abstract: High Asian glaciers and precipitation have directly or indirectly influenced the freshwater supply of billions of people and natural ecosystems in surrounding areas. To better understand the hydroclimatic changes in the High Asian transboundary river basins in the context of global warming, more precipitation‐sensitive proxy data are needed. In this paper, we used the tree‐ring cores of Pinus densata and Picea brachytyla from the southern Tibetan Plateau (TP) to establish a tree‐ring‐width composite chronology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 90 publications
0
2
0
Order By: Relevance
“…Examining dry and wet variations on a broader scale is more advantageous in elucidating spatial hydrological and climatic transformations, and concurrently, it serves to validate the accuracy of precipitation reconstruction (Hannaford et al, 2011; Yue et al, 2022). This study focuses on conducting a comparative analysis of the reconstructed precipitation with hydrological reconstruction sequences in North China and the Yellow River Basin (Figure 7).…”
Section: Discussionmentioning
confidence: 99%
“…Examining dry and wet variations on a broader scale is more advantageous in elucidating spatial hydrological and climatic transformations, and concurrently, it serves to validate the accuracy of precipitation reconstruction (Hannaford et al, 2011; Yue et al, 2022). This study focuses on conducting a comparative analysis of the reconstructed precipitation with hydrological reconstruction sequences in North China and the Yellow River Basin (Figure 7).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the area is considered an excellent location to conduct a dendroclimatology study (Fan et al, 2009). Many efforts have been made to reconstruct historical climate and to find key climate factors affecting tree growth by using tree ring data of typical coniferous tree species in CHM, such as for Abies georgei (Fan et al, 2009;Liang et al, 2010;Panthi et al, 2018), Larix potaninii (Zhang et al, 2017¸ 2020, Picea brachytyla (Fan et al, 2008;Li et al, 2012;Yue et al, 2022), Picea likiangensis (Wang et al, 2018;Yu et al, 2018;Du et al, 2020), and Tsuga dumosa (Guo G. et al, 2009;Li et al, 2011;Aryal et al, 2020). These studies found that tree radial growth was influenced by both temperature and precipitation, but the growth response pattern was depended on species characteristics and site conditions.…”
Section: Introductionmentioning
confidence: 99%